The Impact of Distance Education during the COVID-19 Pandemic on Physical Activity and Well-Being of Czech and Polish Adolescents - Frömel, Karel; Groffik, Dorota; Valach, Petr; ŠafáŘ, Michal; MitáŠ, Josef (The Journal of school health, 2022)
BACKGROUND: The aim of this study was to identify the changes in the structure of weekly physical activity (PA) and well-being among adolescent boys and girls between habitual education (HE) and distance education (DE) during the pandemic in secondary schools. METHODS: The research was carried out in 12 Czech and 18 Polish schools during 2019 to 2020 academic session for HE and 2020 to 2021 academic session for DE. The research involved 723 girls and 626 boys aged 15 to 18 years. The structure of the weekly PA was assessed using the International Physical Activity Questionnaire-Long Form, while well-being was assessed using the World Health Organization-5 Well-Being Index. RESULTS: There was a statistically significant decrease of PA among boys in school PA, transportation PA, recreation PA, vigorous PA, moderate PA, walking, and overall weekly PA during the DE resulting from the pandemic. In girls, during DE, a decrease was observed in school PA, vigorous PA, and overall PA. During DE, a high level of well-being was reported by only 34.9% of girls (43.8% during HE) and 50% of boys (65.6% during HE). CONCLUSIONS: The observed low PA and high incidence of depressive symptoms in adolescents in distance education during pandemic constraints are a challenge for schools to change in supporting physical activity, eliminating similar negative impacts on school life in the future.
Keywords: symptoms of depression; Male; Education, Distance; Adolescent; Poland; Česká republika; distance education; mužské pohlaví; pandemie; Exercise; Covid-19; physical activity recommendations; sedentary behavior; mladiství; Czech Republic; mental health; Schools; školy; lidé; ženské pohlaví; Humans; Pandemics; Female; Polsko; cvičení; COVID-19; distanční studium